MINAT MAHASISWA TATA RIAS AKS-AKK YOGYAKARTA UNTUK MENGIKUTI UJI KOMPETENSI - Herina Yuwati; Tri Warsihapsari (Jurnal Socia Akademika, 2022)
This study aims to find out how much interest students have in participating in competency tests in any field the field of Cosmetology. To take the competency test as a personal need to increase knowledge, experience, and skills or as a compulsion because when you graduate, you must already have a competency test certificate sheet. This research is descriptive because it tries to describe and interpret objects as they are. The research subjects were determined by sampling technique. The panelists consisted of 51 make-up students consisting of 24 students in the third semester of make-up and 27 in the fifth semester of make-up. In collecting data using interview techniques, observation, and documentation. Observations and interviews were used to obtain detailed data about students' interest in the competency test. While documentation is used to describe when students take practical competency tests to make it look real. Data were analyzed using descriptive analysis techniques. The results of the study show that there are groups of students who take the competency test as a necessity to add knowledge, insight, skills, and experience for their benefit. Some of the other groups took the competency test because it was a requirement as a requirement for a Diploma Companion Certificate (SKPI).